2020
DOI: 10.31236/osf.io/vesh3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining wearable sensor signals, machine learning and biomechanics to estimate tibial bone force and damage during running

Emily Matijevich,
Leon R. Scott,
Peter Volgyesi
et al.

Abstract: There are tremendous opportunities to advance science, clinical care, sports performance, and societal health if we are able to develop tools for monitoring musculoskeletal loading (e.g., forces on bones or muscles) outside the lab. While wearable sensors enable non-invasive monitoring of human movement in applied situations, current commercial wearables do not estimate tissue-level loading on structures inside the body. Here we explore the feasibility of using wearable sensors to estimate tibial bone force du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…For each step, the active force peak was computed separately for each sampling rate. We focused on active peak force from the pressure insoles because we previously found it to be the most important input signal for a wearable sensor system that was trained to estimate peak tibial bone force (Matijevich et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each step, the active force peak was computed separately for each sampling rate. We focused on active peak force from the pressure insoles because we previously found it to be the most important input signal for a wearable sensor system that was trained to estimate peak tibial bone force (Matijevich et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Pressure sensing insoles enable us to measure forces under the feet during activities such as running, which can provide valuable insight into human movement and clinical care (Chuckpaiwong et al, 2008; Dixon, 2008; Hullfish and Baxter, 2020; Mann et al, 2016). For instance, we have previously shown that peak force under the foot, which can be estimated from a pressure insole, is an important input for biomechanical algorithms trained to estimate forces on and understand injury risk to musculoskeletal structures inside the body (Matijevich et al, 2020). Pressure insoles can also be used in real-world data collections outside the laboratory, to collect more data (e.g., more strides), in more realistic and representative environments, and over longer periods than can be achieved in laboratory studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in Table 5, three studies employed data-driven approaches to predict GRF metrics using acceleration data (Komaris et al, 2019;Derie et al, 2020;Tan et al, 2020), and one study used this approach to predict tibial loading force using IMU signals (Komaris et al, 2019). Additionally, three studies were conducted on treadmills (Komaris et al, 2019;Matijevich et al, 2020;Tan et al, 2020), and one was conducted overground (Derie et al, 2020). One study utilized IMU sensors (Tan et al, 2020), one used tri-axial accelerometers (Komaris et al, 2019), and two used virtual accelerometers (Derie et al, 2020;Matijevich et al, 2020), where the acceleration data were derived from kinematic measurements.…”
Section: Data-driving Approachesmentioning
confidence: 99%
“…Notably, the prediction of GRF metrics from inertial sensors using deep learning algorithms has shown high accuracy, as evidenced in studies (Ngoh et al, 2018;Johnson W. R. et al, 2020;Tan et al, 2020). Similarly, projections of inner tibial bone load have been successfully explored through machine learning (Matijevich et al, 2020). Understanding the role of external TA in both external Frontiers in Bioengineering and Biotechnology frontiersin.org impact loading and internal tibial bone loading, therefore, becomes crucial (Matijevich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%